Perspectives of Organic and Perovskite‐Based Spintronics. Issue 14 (19th March 2021) - Privitera, Alberto; Righetto, Marcello; Cacialli, Franco; Riede, Moritz K.
Abstract: Spin‐related phenomena in optoelectronic materials can revolutionize several technological applications in the areas of data processing and storage, quantum computing, lighting, energy harvesting, sensing, and healthcare. A fundamental boost to this promising field can be envisaged thanks to the use of two emerging materials, which have recently been receiving increasing scientific attention: organic semiconductors (OSCs) and halide perovskites (HPs). Here, the first progress in the resulting fields, organic‐ and perovskite‐based spintronics, is reviewed, which will enable the manipulation of spin, charges, and photons in spin/optoelectronic devices. A link between these two classes of materials is created by highlighting the pros and cons of each technology, and their potential applications in new multifunctional spintronic devices are discussed. Current challenges in the field are also outlined, and convenient approaches to overcome them are proposed. Abstract : Organic semiconductors and halide perovskites have received tremendous interest and hold great promise for the commercialization of next‐generation optoelectronic devices. Their unique and complementary spin characteristics could also pave the way for (opto)spintronics, widely expanding their range of possible application. Herein, the spin properties of these materials are reviewed and potential future development of the field is highlighted.